Analysis of Factors Influencing Laptop Purchase Decisions - Nawiyah, Nawiyah; Kurniawati, Renny; Endrawati, Titin (Westscience Press, 2023)
Consumers are currently vying for laptops as desirable electronic goods. Customers consider price, brand, and quality while making laptop purchases. The study's goal covered the considerations while buying a laptop. Utilizing tools from linear regression analysis, the study methodology combines quantitative descriptive methodologies. The Likert scale is used to collect data using SPSS version 27, and 200 students are sampled from the student body of APP Polytechnic who utilize laptops. The t-test results indicate that purchasing decisions are positively and significantly influenced by price, brand image, and quality. The F test findings show that the variables together have a 13.7% influence, with other factors accounting for the remaining 86.3%.